Determination of sports health belief levels of individuals who do sports for recreational purposes - Mustafa Vural; Yasar Coruh (Türk Spor ve Egzersiz Dergisi)
This study was carried out in order to determine sports health belief levels of individuals participating in sporting recreational activities in sports facilities belonging to Konya Metropolitan Municipality in terms of some demographic variables. A method for descriptive survey aimed at revealing the current situation was used in the research. Sample group of the study consists of 150 participants (female = 66 / male = 84) who attend the courses opened in Konya Metropolitan Municipality. In the study, "Sport Health Belief Scale" with 5 sub-dimensions developed by Ertüzün and personal information form developed by the researcher were used. In the analysis of the data, "Kolmogorov-Smirnov" test was performed for normality test and it was determined that data had normal distribution. While comparing data according to normality test in terms of female and male, independent samples T test was used. One-way Anova test was used in multiple comparisons in terms of sport year and age and Tukey test was applied in order to determine difference between the groups because of variance homogeneity. Significance level in the study was determined as =0.05. As a result of the research, when comparisons were examined according to gender variables, there was a significant difference between male and female athletes in terms of perceived seriousness, perceived obstacles, physical benefits and psychological benefits sub-dimensions which are sports health belief scale sub-dimensions, but differences were not determined in self-efficacy sub-dimension. A significant difference was determined in educational status variable. It was determined that perceived seriousness, physical benefits, psychological benefits and perceived obstacles levels of individuals aged 17-20 years were significantly different from individuals aged 26-30 and +30. In sport year variables, it was concluded that perceived seriousness dimension of individuals whose exercise period was between 3 months-1 year was significantly different from those whose exercise period was +2 years and self-efficacy perceptions of individuals who hadn’t done sports were significantly different from those whose exercise period was 3 months-1 year and +2 years.